The Putnam River stories: blankets from 1984 to 1987 - Trottmann, Robert Bruce, author; Lundberg, Thomas R., advisor; Coronel, Patricia D., committee member; Crow, Mary, committee member; Ellerby, David A., committee member; Levine, Frederick S., committee member (Colorado State University. Libraries, 1987)
The blankets are about birds, rivers, deer, and sticks. They are about the stages: life, death, birth, and rebirth. They describe walking crippled and not walking at all, fences, stairways, barriers, and protection. They represent covering up, exposure, enclosure, and warmth. The blankets are hideouts, places of escape. Creating a sacred space, the blankets promote mystical awareness, magical experience, and a realm of preciousness. Their process of creation is ritualistic, as is their use. Ritual use augments the magic, promotes transformation, and induces transcendence. Unifying the physical and nonphysical, the blankets serve the body and the mind. It is important that the blankets offer hope. So they may be personally and socially enlightening, they must contain tremendous sadness, pain, and images of death and loss. Through repose they embody wholeness. Pictorial images on the blankets are created with embroidery. The process of embroidery is technically simple and proportionate to the construction requirements of the blankets. With embroidery I create symbols of personal and universal origin to contact essences. These symbols also explain and contact the past and present either metaphorically or directly. The blankets are an expression of values and a confirmation of social responsibility. Within the blankets issues and questions regarding time, states of consciousness, location, domesticity, health, aging, and interpersonal relationships are personified. Through the interaction and exchange between myself, needle and thread, and ground cloth, there results an endorsement of things made by hand. Because it is ancient, the technique of embroidery and hand sewing, with its requirement of extended contact with the materials imbues the blankets with an energy which can and does affect users of the blankets. Being made by hand, the blankets promote the power and mystery of touch and connect the blankets with the larger forces which created the hand. The blankets are the result of natural forces. They are organic. They are born, are now alive, and eventually will die. Cloth and threads are familiar to everyone. Both are essentially universal. I select materials with great care using intuitive processes. Color, weight, texture, thickness, and tactile responses are vital considerations for me. Due to the familiarity of the materials the blankets are capable of speaking to a large and diverse audience. The blankets may accurately be called shrouds or robes. The dynamics of their movement in use is contingent on the willingness, curiosity, and imagination of the user. The blankets' vitality is fully expressed when adorned by a user. The blankets may be sat under, slept with, lain upon, or wrapped around. Their posture, in use is dependent on a person's body, alive or dead. If the blankets cannot be used in life, they are viable as shrouds. It is the mystical, ritualistic, and transcendent power of the blankets that attracts and propels me in exploring new possibilities within this traditional format.
Keywords: Life in art; Textile fabrics in art; Symbolism in art